Розвиток і життєвість ценопопуляцій домінуючих деревних видів в умовах дендропарку “Тростянець” - Ilyenko, O.O.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
In the article were described and revealed the results of long-term examinations of dynamics of number and age structure of populations of 14 dominant species of park dendrocenosis as well as the comparative quantitative assessment of the degree of their dynamics and the intensity and direction of dynamic processes of examined populations as well. The expediency of carrying out of examinations of park dendrocenosis under populations level is emphasized.